Developing a Canadian-Specific Version of the Fitness-to-Drive Screening Measure©. (April 2016) - Classen, Sherrilene; Alvarez, Liliana; Ferreira, Peter J. M.; Chen, Chien H.; Meyer, Carly K.; Nywening, Amy G.
The Fitness-to-Drive Screening Measure © (FTDS) is a valid and reliable screening tool that identifies at-risk older drivers. Although 12, 300 Canadians have used the FTDS in the last 2 years, the resources/recommendations targeted the U.S. context. The objective of this article is to identify the FTDS resources/recommendations appropriate for Canadian users and the barriers that Canadian stakeholders experience when promoting older driver fitness. Twenty stakeholders from three provinces (eight occupational therapists, three certified driver rehabilitation specialists, four physicians, and five members of advocacy organizations) participated in semi-structured interviews. We conducted summative and thematic content analysis. A comprehensive set of resources/recommendations was identified. Barriers to older driver fitness decisions included fear of losing the license, compromising the physician–client relationship, insufficient training/resources for health care professionals, and inadequate alternative transportation. Canadian context-specific resources/recommendations were integrated into a Canadian version of the FTDS. This version may better serve Canadian older drivers, caregivers, and health care professionals.